Solving Three Dimensions Volterra Integral Equations (TDVIE) via a Neural Network - Nahdh S. M. Al-Saif; Ameen Sh. Ameen; Ghaith Fadhil Abbas (Tikrit Journal of Pure Science, 2019)
The aim of this paper  is present a new numerical method for solvingThree Dimensions Volterra Integral Equations using artificial neural network by design multilayer feed forward Neural Network. A multi- layers design in our proposed method consist of a hidden layer having seven hidden units. and one linear output unit. Linear Transfer function used as each unit and using Levenberg- Marquardtalgorithmtraining. Moreover, examples on three- dimensional Volterra integral equations carried out to illustrate the accuracy and the efficiency of the presented method. In addition, some comparisons among proposed method and Shifted Chebyshev Polynomials method and Reduced Differential Transform Method are presented